Advancing Photovoltaic Module Inspection: The Power of UV Imaging for Comprehensive Material Analysis and Quality Assurance - Buerhop, Claudia; Van Dyk, Ernest E.; Vorster, Frederik J.; Stroyuk, Oleksandr; Mashkov, Oleksandr; Crozier McCleland, Jacqueline L.; Vumbugwa, Monphias; Hauch, Jens; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2024)
This study highlights the versatile applications of UV fluorescence imaging for solar park inspection. Beyond visualizing cell cracks, UV imaging efficiently classifies backsheet (BSh) types, assesses EVA degradation, and correlates with corrosion and insulation issues without system interruption. Utilizing a 1 MWp solar power plant as an example, UV imaging on 558 PV modules reveals three distinct patterns correlating with NIRA-identified BSh types. Critical issues, affecting 12.8% of modules with PET-based, multilayered BShs with a fluorinated coating (FC-PET-PP), include cracks, corrosion, and severe insulation problems (Riso < 8 MΩ) for 27% of strings. The results, achieved with a throughput rate of 220 modules per hour, underscore UV imaging's efficacy in discerning nuanced module conditions. Scaling this holistic approach promises statistically significant insights into PV system performance. The study advocates for elevated decision-making and maintenance strategies in the solar energy sector, emphasizing the transformative potential of UV imaging for comprehensive solar module assessments.
CRIS-Team Scopus Importer:2025-02-04